Theory of constraints contributions to outbound logistics - de Souza, Fernando Bernardi [UNESP]; Pires, Sílvio R.I. (Emerald, 2010)
Purpose: The purpose of this paper is to systematically describe the key practical contributions of the theory of constraints (TOC) to outbound (distribution) logistics. Design/methodology/approach: Based on theoretical research, this paper presents the main practical aspects of the approach suggested by TOC to outbound logistics and discusses the assumptions upon which it is based. Findings: This paper corroborates the thesis defended by TOC, according to which the current ways of managing outbound logistics, based mainly on sales forecasts lead to difficulties in handling trade-offs between logistics (stock and transportation) costs and stock-out levels. Research limitations/implications: The reported research is of a theoretical nature. Practical implications: TOC offers a proposal that is complementary in many aspects and very distinguishable in others about the way some key processes and elements of supply chain management (SCM) are managed, especially outbound logistics. Originality/value: Considering the dearth of papers dealing with the conceptual articulation and organization of this subject, the paper contributes to systematize the knowledge currently available about the contributions of the TOC to outbound logistics, highlighting the practical implications of applying TOC to outbound logistics. © Emerald Group Publishing Limited.
Keywords: Costs; Distribution management; Lead times; Order systems; Stock control